2011
DOI: 10.1038/eye.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus following retinal detachment repair: a comparison between scleral buckling and vitrectomy procedures

Abstract: Purpose We conducted a study to investigate: (1) deviations caused by retinal detachment (RD) repair; (2) correlation between visual acuity and the number of surgeries to deviation size; and (3) differences between deviations following scleral buckling (SB) and pars plana vitrectomy (PPV). Methods A retrospective analysis of patients with persistent binocular diplopia following RD repair. Magnitude of manifest deviation (|dev|) in the primary position (PP) and position of greatest deviation (maxDev) was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
4
2
Order By: Relevance
“…Previous studies, though, have shown a similar incidence between SB and PPV, with SB patients having slightly larger prismatic deviations. [14] Additionally, the type of anesthesia may play a role in postoperative strabismus with direct inoculation of the rectus muscle with anesthesia, however, we did not see an effect on postoperative strabismus in our series between the types of anesthesia (retrobulbar versus sub-tenon's versus general anesthesia, p = 0.15).…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies, though, have shown a similar incidence between SB and PPV, with SB patients having slightly larger prismatic deviations. [14] Additionally, the type of anesthesia may play a role in postoperative strabismus with direct inoculation of the rectus muscle with anesthesia, however, we did not see an effect on postoperative strabismus in our series between the types of anesthesia (retrobulbar versus sub-tenon's versus general anesthesia, p = 0.15).…”
Section: Discussioncontrasting
confidence: 59%
“…6 A study proposed that when there are no obvious restrictions to eye movements or a reported macular translocation, patients who had weak fusional reserves before the retinal detachment may experience post-operative diplopia because they do not having the capacity to adapt following surgery. 7 From the UHG experience it can be stated that all patients experienced vertical diplopia rather than horizontal diplopia, and this could be linked to smaller vertical fusional reserves. This experience is similar to a study of 821 patients who underwent scleral buckling surgery: post-operatively 12 patients developed diplopia (1.5%), with 10 of these reporting vertical diplopia (83%).…”
Section: Discussionmentioning
confidence: 99%
“…The strabismus that developed following scleral buckling showed no significant difference in magnitude when measured in the primary position to that measured post-vitrectomy, however the ocular deviation was significantly greater when comparing the maximum deviation measured between the two groups. 19 Torsional diplopia was a consequence of macula translocation. Sato reported on 32 patients, 5 having peripheral fusion and 3 with gross stereopsis.…”
Section: Incidencementioning
confidence: 99%